Data from: Comparative population genomics reveals key barriers to dispersal in Southern Ocean penguins - Clucas, Gemma V.; Younger, Jane L.; Kao, Damian; Emmerson, Louise; Southwell, Colin; Wienecke, Barbara; Rogers, Alex D.; Bost, Charles-Andre; Miller, Gary D.; Polito, Michael J.; Lelliot, Patrick; Handley, Jonathan; et al. (Dryad, 2018)
The mechanisms that determine patterns of species dispersal are important factors in the production and maintenance of biodiversity. Understanding these mechanisms helps to forecast the responses of species to environmental change. Here we used a comparative framework and genome-wide data obtained through RAD-seq to compare the patterns of connectivity among breeding colonies for five penguin species with shared ancestry, overlapping distributions, and differing ecological niches, allowing an examination of the intrinsic and extrinsic barriers governing dispersal patterns. Our findings show that at-sea range and oceanography underlie patterns of dispersal in these penguins. The pelagic niche of emperor (Aptenodytes forsteri), king (A. patagonicus), Adélie (Pygoscelis adeliae) and chinstrap (P. antarctica) penguins facilitates gene flow over thousands of kilometres. In contrast, the coastal niche of gentoo penguins (P. papua) limits dispersal, resulting in population divergences. Oceanographic fronts also act as dispersal barriers to some extent. We recommend that forecasts of extinction risk incorporate dispersal and that management units are defined by at-sea range and oceanography in species lacking genetic data. Adelie penguins - VCF of SNP datasetAdelie.vcfChinstrap penguins - VCF of SNP datasetChinstrap.vcfGentoo penguins - VCF of full SNP datasetincludes outlier lociGentoos_all-SNPs.vcfGentoo penguins - VCF of neutral SNP datasetoutlier loci removedGentoos_neutral-SNPs.vcfGentoo penguins - nexus file for BFD*Input file of SNPs for BFD* species delimitationGentoos_input_for_BFD.nexGentoo penguins - phylip file for RAxMLPhylip alignment of SNPs for phylogenetic inference in RAxMLGentoos_input_for_RAxML.phyGentoos_input_for_SNAPP_set1XML input file for SNAPP analysis of gentoo penguins - set 1Gentoos_input_for_SNAPP_set2XML input file for SNAPP analysis - set 2